Immunogenicity of full-length P. vivax rPvs48/45 protein formulations in BALB/c mice. Issue 1 (3rd January 2022) - Arévalo-Herrera, Myriam; Miura, Kazutoyo; Solano, Eduardo; Sebastián Ramírez, Juan; Long, Carole A.; Corradin, Giampietro; Herrera, Sócrates
Abstract: Background: Pvs 48/45 is a Plasmodium vivax gametocyte surface protein involved in the parasite fertilization process. Previous studies showed that Pvs 48/45 proteins expressed in Escherichia coli ( E. coli ) and Chinese hamster ovary (CHO) cells were highly immunoreactive with sera from malaria-endemic areas and highly immunogenic in animal models. Here the immunogenicity in mice of three different vaccine formulations was compared. Methods: Recombinant (r) Pvs 48/45 proteins were expressed in E. coli and CHO, purified, formulated in Alhydrogel, GLA-SE and Montanide ISA-51 adjuvants and used to immunize BALB/c mice. Animals were immunized on days 0, 20 and 40, and serum samples were collected for serological analyses of specific antibody responses using ELISA and immunofluorescence (IFAT). Additionally, ex-vivo transmission-reducing activity (TRA) of sera on P. vivax gametocyte-infected human blood fed to Anopheles albimanus in direct membrane feeding assays (DMFA) was evaluated. Results: Most immunized animals seroconverted after the first immunization, and some developed antibody peaks of 10 6 with all adjuvants. However, the three adjuvant formulations induced different antibody responses and TRA efficacy. While GLA-SE formulations of both proteins induced similar antibody profiles, Montanide ISA-51 formulations resulted in higher and longer-lasting antibody titers with CHO-r Pvs 48/45 than with the E. coli formulation. Although the CHO protein formulated in Alhydrogel generated a high initial antibody peak, antibody responses to both proteins rapidly waned. Likewise, anti- Pvs 48/45 antibodies displayed differential recognition of the parasite proteins in IFAT and ex vivo blockade of parasite transmission to mosquitoes. The CHO-r Pvs 48/45 formulated in Montanide ISA-51 induced the most effective ex vivo parasite blockage. Conclusions: Three out of six vaccine formulations elicited antibodies with ex vivo TRA. The CHO-r Pvs 48/45 Montanide ISA-51 formulation induced the most stable antibody response, recognizing the native protein and the most robust ex vivo TRA. These results encourage further testing of the vaccine potential of this protein.